2021
DOI: 10.3390/coatings11020223
|View full text |Cite
|
Sign up to set email alerts
|

Bodipy-Loaded Micelles Based on Polylactide as Surface Coating for Photodynamic Control of Staphylococcus aureus

Abstract: Decontaminating coating systems (DCSs) represent a challenge against pathogenic bacteria that may colonize hospital surfaces, causing several important infections. In this respect, surface coatings comprising photosensitizers (PSs) are promising but still controversial for several limitations. PSs act through a mechanism of antimicrobial photodynamic inactivation (aPDI) due to formation of reactive oxygen species (ROS) after light irradiation. However, ROS are partially deactivated during their diffusion throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…In addition to recent examples such as the hypericin loaded liposomes against Gram(+) bacteria [282][283][284][285][286], another emerging and promising alternative includes the development of modified liposome-like derivatives labeled either as "ethosomes", "transfersomes", or "invasomes", which can be briefly described as ultra-deformable vesicular carriers with upgraded transdermal penetration and increased permeability into the skin for the PSs compared with conventional liposomes [287][288][289][290]. On the other hand, recently reported aPDT micellar systems refer to micelles loaded with various hydrophobic PSs such as curcumin, BODIPY, porphyrins, hypocrellin A, or hypericin among others [121,[291][292][293]. Furthermore, solid lipid NPs (SLN) composed of solid biodegradable lipids have been recently highlighted as delivery systems used for actual mRNA COVID-19 vaccines [294], but they also have been reported as transporters for curcumin for the treatment of oral mucosal infection [121].…”
Section: Lipid-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to recent examples such as the hypericin loaded liposomes against Gram(+) bacteria [282][283][284][285][286], another emerging and promising alternative includes the development of modified liposome-like derivatives labeled either as "ethosomes", "transfersomes", or "invasomes", which can be briefly described as ultra-deformable vesicular carriers with upgraded transdermal penetration and increased permeability into the skin for the PSs compared with conventional liposomes [287][288][289][290]. On the other hand, recently reported aPDT micellar systems refer to micelles loaded with various hydrophobic PSs such as curcumin, BODIPY, porphyrins, hypocrellin A, or hypericin among others [121,[291][292][293]. Furthermore, solid lipid NPs (SLN) composed of solid biodegradable lipids have been recently highlighted as delivery systems used for actual mRNA COVID-19 vaccines [294], but they also have been reported as transporters for curcumin for the treatment of oral mucosal infection [121].…”
Section: Lipid-based Systemsmentioning
confidence: 99%
“…Among examples, an aPDT system of polymeric micelles, fabricated from methoxy-PEG and PCL and loaded with the hydrophobic PS curcumin and ketoconazole for the PDI of fungal biofilms, has been reported with an increased water solubility and controlled release of the PSs on display [380]. Additionally, Caruso et al recently reported the synthesis of thermodynamically stable PEG-PLA micelles for efficient aPDI of S. aureus, suggesting that this delivery system is promising in aPDI applications, which also reduces toxicity compared with pure PSs [291]. Moreover, a significant advantage of polymeric micelles compared with lipid-based micelles resides notably in the adjustability of properties by individual design of the polymer and membrane surface with respect to the selected application.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…PDT provoked a certain damage to embedded PAO1 cells, suggesting that they could be more sensitive to other antimicrobial agents delivered upon photodynamic treatment. The embedding of porphyrins in nanoparticles or polymeric coatings could be exploited both for skin disinfection and surface sanitization [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Even in the case of BODIPYs this type of approach is extremely important for their application in PDT [ 40 , 71 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ].…”
Section: Bodipys Studiesmentioning
confidence: 99%